Precarity in European Film Depictions and Discourses - Cuter, Elisa; Kirsten, Guido; Prenzel, Hanna (Film, Class, Society, 2022)
This volume explores how contemporary European cinema engages with the increasing precarization of life and work on the continent. It compares how the filmic traditions of different countries reflect the socioeconomic conditions associated with precarity, and sheds light on the recurring tropes, themes, narratives, and genre conventions that shape its representation.